How does diversity manifest itself in software ecosystems? - Outão, Juliana Carvalho Silva do; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2022)
Context: Diversity has been addressed in software ecosystem studies in recent years, aiming at the inclusion and collaboration of different groups within organizations and communities. Its several forms of manifesting have required a better understanding of its effects on the ecosystem. Problem: Since an ecosystem involves the interaction of actors over a common technological platform that supports software solutions or services, the diversity and the relationships between different actors remain a challenge, especially in order to sustain the ecosystem and stimulate its growth. Solution: This study aims to understand how diversity manifests itself in the ecosystem context, based on the existing studies. IS Theory: The research was developed under the aegis of the General Systems Theory, focusing on the relationships between the elements of the system. Method: A systematic mapping study was carried out to identify and characterize how diversity in ecosystems has been discussed, which approaches have been applied and which effects are observed. Results: Based on 13 selected studies, we observed that the most discussed type is demographic diversity and the subtype is gender diversity. It was also noticed that gender diversity increases the productivity of development teams, despite the fact that they are still mostly male. Additionally, an analysis was carried out on how these studies discuss diversity in light of the 15 human, technical and organizational factors of ecosystems. Contribution: The five factors that most affect diversity in ecosystems were identified and actionable approaches were suggested to increase diversity in ecosystems, contributing to the Grand Research Challenge in Information Systems “Information Systems and the Open World Challenges”.